INVESTIGATING THE OBSTACLES OF PARENTS IN ACCOMPANYING THEIR CHILDREN DURING LEARNING FROM HOME AT SMP CATHOLIC DON BOSCO TOLITOLI - Ismail Yunus; Gabriella Febriani Dossy (Universitas Madako Tolitoli, 2022)
This research aims to know the obstacles experienced by parents in accompanying their children during learning from home at SMP Catholic Don Bosco Tolitoli. This research is descriptive qualitative. Researcher used interviews with parents to collect the data. There were 6 parents of Catholic junior high school student Don Bosco as the sample. The results of this research show that in general the obstacles of parents in accompanying children during learning from home are difficult to provide technology facilities, bad networks as obstacles, do not have enough time in accompanying children learning from home, children are not focused on learning, parents are difficult to explain the material.